P-195 Do the presence of necrotic foci and/or separate blastomeres, the blastocoele expansion degree affect pregnancy outcomes of frozen-thawed euploid blastocysts transfer cycles?. (30th June 2022) - Ozer, G; Akca, A; Yuksel, B; Duzguner, I; Kahraman, S
Abstract: Study question: Do the presence of necrotic foci and/or the presence of separate blastomeres and the blastocoele expansion degree affect pregnancy outcomes of frozen-thawed euploid embryo transfer cycles? Summary answer: Significant correlations were observed between pregnancy outcomes and the degree of blastocoele expansion, the presence of necrotic foci or separate blastomeres in the euploid embryo. What is known already: Implantation failure and pregnancy losses may occur despite the selection of a healthy euploid embryo for transfer and the elimination of other risk factors. Blastocyst morphology is known to affect pregnancy outcomes, but the effect of necrotic foci and/or separate blastomeres in the embryo on pregnancy outcomes needs further investigation. Study design, size, duration: This is a retrospective cohort study and was conducted at ART and Reproductive Genetics Centre, Memorial, Sisli Hospital, Istanbul, Turkey between January 2017 and September 2021. A total of 2758 frozen-thawed euploid embryo transfer cycles were included in the study. Participants/materials, setting, methods: After thawing, the embryos were divided into groups according to their morphological grades, whether there were necrotic foci and whether there were separate blastomeres, and were evaluated in terms of pregnancy outcomes. Blastocysts were graded by using Gardner and Schoolcraft's grading system. Ongoing pregnancy was defined as a pregnancy that had reached 20 weeks. Miscarriage was defined as a pregnancy loss occurring before the 20th gestational week. Main results and the role of chance: Our data showed that the presence of necrotic foci in the inner cell mass or trophectoderm reduced the ongoing pregnancy rates and increased the miscarriage rates. The ongoing pregnancy rate was lower (41.0%, vs 60.0%, p < 0.001) and the miscarriage rate was higher (27.3% vs 19.8%, p < 0.05) in the group with necrotic foci than in the group without necrotic foci. The presence of separate blastomeres decreased the ongoing pregnancy rates (50.3% in the group with separate blastomeres, 61.8% in the group without separate blastomeres) (p < 0.001) and increased the miscarriage rates (25.3% in the group with separate blastomeres, 18.8% in the group without separate blastomeres) (p > 0.004). The ongoing pregnancy rates for blastocoele expansion degrees of 2, 3, 4, 5, and 6 were 39.5%, 38.3%, 59.3%, 59.8%, and 61.4%, respectively and the miscarriage rates for blastocoele expansion degrees of 2, 3, 4, 5, and 6 were 35%, 33.3%, 21%, 21.2%, 18.4%, respectively. Embryos with degrees of expansion grade ≤ 3 had lower ongoing pregnancy rates and higher miscarriage rates than those with degrees of expansion > 3 (p < 0.01). Limitations, reasons for caution: Retrospective study. Wider implications of the findings: When choosing the embryo to be transferred in cases with more than one euploid embryo, the selection should be made by considering the blastocoele expansion degrees and the presence of necrotic foci and separate blastomeres in the embryo. Trial registration number: not applicable